MAKNA IDENTITAS PUNK MUSLIM PULOGADUNG - Mike Indarsih (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2016)
ABSTRACTThis research aims to know The meaning of Identity of Muslim Punk Pulogadung. How does the meaning of Punk Muslims present inside the recidents who eventually formed action for the muslim punk scene in the community. The research method used is the method of symbolic interaction of Herbert Blumer, first premis with three human beings act toward things based on the meaning on something that for them, the second meaning is derived from a person’s social interaction with people another. Third, the meaning of enhanced through a process of social interaction. The results of the study found that ini the communication process of Muslim Punk. Thre is an element of the message sender message, media, message recipients who eventually obtain meaning together, meaning Punk Muslims ultimately divided into two, a true muslim and a punk muslim genre action. Where the first meaning the absence of identity of punk thet ends up as a true muslim, while the second meaning is a genre of Punk Muslim Punk identity but still inside there is the meaning of punk that has GOD. Keywords : Process, Muslim Punk, Identity, Transformation ABSTRAKPenelitian ini bertujuan untuk mengetahui Makna Identitas Punk Muslim Pulogadung, bagaimana makna Punk Muslim hadir dalam diri para penghuni yang akhirnya membentuk tindakan bagi Punk Muslim dalam masyarakat. Metode penelitian yang digunakan adalah metode interaksi simbolik Herbert Blumer dengan tiga premis yang pertama Manusia bertindak terhadap sesuatu berdasarkan makna yang ada pada sesuatu itu bagi mereka, kedua, makna tersebut berasal dari interaksi social seseorang dengan orang lain, ketiga, makna tersebut disempurnakan melalui proses interaksi social. Hasil penelitian menemukan bahwa dalam proses komunikasi Punk Muslim terdapat unsur pengirim pesan, pesan, media, penerima pesan yang akhirnya memperoleh makna, makna Punk Muslim akhirnya terbagi menjadi dua yaitu makna muslim sejati, dimana makna ini tanpa adanya identitas Punk dan berakhir sebagai muslim sejati sedangkan makna kedua Punk yang bergenre muslim, dan masih adanya identitas Punk namun didalamnya terdapat makna Punk yang memiliki Tuhan. Kata kunci : Proses komunikasi, Punk Muslim, Transformasi, Identitas.